Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1879)
Keywords: 18.Bookworm; 2.Damage

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1879)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1879)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1879)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Collegii Salmanticensis Fr. Discalceatorum B. Mariae d Monte Carmeli Parenti suo Eliae conscrati Cursus Theologicus (Apud Victorem Palme, Bibliopolam, 1879)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Decreta Autentica Congregationis Sacrorum Rituum Ex Actis Eiusdem Collecta (Typis S. Congregationis de Propaganda Fide, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1879)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Historia de uma administração ultramarina (Typ. de J.G. De Sousa Neves, 1879)
OCLC: 26057296
Keywords: 10.Cover Damage; 2.Damage; Colonies Administration; Condition: Fair; History; Portugal Colonies; Portuguese colonies

Litterae Encycliae, Aeterni Patris" Leonis Papae XIII, De Philosophia Scholastica (Commissio Synodalis in Sinis, 1879)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Sainte Jeanne-Francoise Fremyot de Chantal sa vie et ses Oeuvres (E. Plon et Cie, Imprimeurs- Editeurs, 1879)
Keywords: 1.Conservation 保護; 18.Bookworm

Scriptorum Veterum de Eucharistia (Libraria Academica Wagneriana, 1879)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Theologia Moralis S. Alphonsi M. De Ligorio (Ex Typis Hyacinthi Marietti, 1879)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Historia da Egreja Catholica em Portugal - Amado, Jose de Sousa (na Typographia De G. M. Martins, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Docvmenta Historiam Ecclesiae Habessionrum - Barreto, Ionnes A. Da Graca (Ex Typographia Nationali, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Historia da Beata Margarida Maria - Bougaud, Padre (1879)
Keywords: 1.Conservation 保護; 2.Damage

Codigo civil portuguez approvado por carta de lei de 1 de julho de 1867 - Castello Branco, Alipio Freire de Figueiredo Abreu (Imprensa nacional, 1879)
OCLC: 904049643
Keywords: Condition: Fair; Hard Cover; Law; Law Portugal

Precis Philosophie - Ch. Benard (Librairie Ch. Delagrave, 1879)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; Philosophy

Historia Popular dos Papas - Chantrel, J. (Livraria Editora de Texixeria de Fretas, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬.; 18.Bookworm; 2.Damage

O Confessor da Infancia e da Mocidade - Cros, Padre (1879)
Keywords: 1.Conservation 保護; 2.Damage

Historiae Seu Vitae Sanctorum - D.D. Laurentio Gastaldi (EX TYPOGRAPHIA PONTIFICIA, 1879)
Keywords: Fair

Traite Elementaire de Physique, Theorique et Experimentale - Daguin, P. A. (Librairie Ch. Delagrave, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Les Auteurs grecs expliqués d'après une méthode nouvelle, par deux traductions françaises ... Denys d'Halicarnasse. Première Lettre à Ammée. [Traduit par MM. F. de Parnajon et H. Weil.] - Denys d'Halicarnasse (Hachette, 1879)
OCLC: 457646667
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Literature

Les Auteurs grecs expliqués d'après une méthode nouvelle, par deux traductions françaises ... Denys d'Halicarnasse. Première Lettre à Ammée. [Traduit par MM. F. de Parnajon et H. Weil.] - Denys d'Halicarnasse (Hachette, 1879)
OCLC: 457646667
Keywords: 18.Bookworm; Condition: Fair; Literature

Les Auteurs grecs expliqués d'après une méthode nouvelle, par deux traductions françaises ... Denys d'Halicarnasse. Première Lettre à Ammée. [Traduit par MM. F. de Parnajon et H. Weil.] - Denys d'Halicarnasse (Hachette, 1879)
OCLC: 457646667
Keywords: 18.Bookworm; Condition: Fair; Literature

Casavant Frères - F. Nadeau, Bertin (Casavant Frères, 1879)
advertisement printing

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1879)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Hard Cover; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1879)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Hard Cover; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin

As Tres Rosas dos Escolhidos - Francisco de Azeredo Teixeira de Aguilar (Typ. da Palavra, 1879)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Critica a Critica - Freitas, Padre Senna (Manoel Malheiro, Editor, 1879)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Svrivs, Historiae seu Vitae Sanctorum - Gastaldi, D. D. Laurentio (Ex Pyopgraphia Pontificia et Archiepiscopali, 1879)
Keywords: 1.Conservation 保護; 2.Damage

Sanctorum Patrum Opusula Selecta - H. Hurter (Libraria Academica Wagneriana, 1879)
Stamp
Keywords: 22.stamp; Condition: Fair; Religion

Sanctorum Patrum, Opuscula Selecta - Huter, H. (Libraria Academica Wagneriana, 1879)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 14.Missing area; 2.Damage; 6.Yellowing 變黃

Éloge de tous les saints martyrs, édition revue et annotée par M. l'abbé C. Appert .. - Jean Chrysostome (Poussielgue frères, 1879)
OCLC: 457530936
Keywords: Condition: Fair

Chorographia moderna do reino de Portugal - João Maria Baptista (Typographia da Academia Real das Sciencias, 1879)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; History

The history of England: from the first invasion by the Romans to the accession of William and Mary in 1688 - Lingard, John (D. & J. Sadlier & Co., 31, Barclay Street: Montreal, 1879)
OCLC: 37067039
Keywords: Condition: Fair; Grande-Bretagne Histoire; Great Britain; Great Britain History; Hard Cover; History

The history of England: from the first invasion by the Romans to the accession of William and Mary in 1688 - Lingard, John (D. & J. Sadlier & Co., 31, Barclay Street: Montreal, 1879)
OCLC: 37067039
Keywords: Condition: Fair; Grande-Bretagne Histoire; Great Britain; Great Britain History; Hard Cover; History

Panorama Des Predicateurs Ou Repertoire Pour L'improvisation et La Composition Du Sermon - M. l'Abbe C. Martin (Librairie Religieuse Et Ecclesiastique De Martin neveu et Audier, 1879)
Keywords: 16.Waterstains; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Panorama Des Predicateurs Ou Repertoire Pour L'improvisation et La Composition Du Sermon - M. l'Abbe C. Martin (Librairie Religieuse Et Ecclesiastique De Martin neveu et Audier, 1879)
Keywords: 10.Cover Damage; 16.Waterstains; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Les enseignements de N.-D. de Lourdes - M. L' Abbé Gineset (Societe Generale de Librairie Catholique, 1879)
stamp of seminario de s. jose
Keywords: 2.Damage; Fair

Homelie Aux Jeunes Gens - Marin, M. L'abbe (Libraie Poussiel gue Preres, 1879)
Keywords: 1.Conservation 保護; 15.Stain 污漬

A Raccolta ou Colleccao de oracoes e obras pias - Seabra, Francisco Luiz de (Ernesto Chardron, 1879)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Curso de Philosophia Elementar para Uso Das Escholas - Sousa, Joaquim Alves de (Imprensa da Universidade, 1879)
Stamp
Keywords: 1.Conservation 保護; 16.Waterstains; 18.Bookworm; 2.Damage

Historiae ecclesiasticae compendium: praelectionibus publicis accomodatum et in tomes tres distributum - Wouters, Henrici Guilielmi (Vanlinthout Fratres, 1879)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Church history; Condition: Fair; Hard Cover; History; church history; Église Histoire